DNases improve effectiveness of antibiotic treatment in murine polymicrobial sepsis - Willemsen, Jan-Fritjof; Wenskus, Julia; Lenz, Moritz; Rhode, Holger; Trochimiuk, Madgalena; Appl, Birgit; Pagarol-Raluy, Laia; Börnigen, Daniela; Bang, Corinna; Reinshagen, Konrad; Herrmann, Martin; Elrod, Julia; et al. (Frontiers in Immunology, 2024)
Introduction: Neutrophil extracellular traps (NETs) have various beneficial and detrimental effects in the body. It has been reported that some bacteria may evade the immune system when entangled in NETs. Thus, the aim of the current study was to evaluate the effects of a combined DNase and antibiotic therapy in a murine model of abdominal sepsis.Methods: C57BL/6 mice underwent a cecum-ligation-and-puncture procedure. We used wild type as well as knockout mice with the same genetic background (PAD4-KO, DNase1-KO). Mice were treated with (I) antibiotics (Metronidazol/Cefuroxime), (II) DNAse1 or (III) with the combination of both; mock-treated mice served as controls. We employed a streak plate procedure as well as 16s-RNA analysis, to evaluate bacterial translocation and quantified NETs formation by ELISA and immune fluorescence. Western blot and proteomics analysis were used to determine inflammation.Results: A total of n=73 mice were used. Mice that were genetically unable to produce extended NETs or were treated with DNases displayed superior survival and bacterial clearance as well as reduced inflammation. DNase1 treatment significantly improved clearance of gram-negative bacteria and survival rates. Importantly, the combination of DNase1 and antibiotics reduced tissue damage, neutrophil activation and NETs formation in the affected intestinal tissue.The combination of antibiotics with DNase1 ameliorates abdominal sepsis.Gram-negative bacteria are cleared better when NETs are cleaved by DNase1. Future studies on antibiotic therapy should be combined with anti-NETs therapies.